Exploring the application and challenges of fNIRS technology in early detection of Parkinson’s disease - Hui, Pengsheng; Jiang, Yu; Wang, Jie; Wang, Congxiao; Li, Yingqi; Fang, Boyan; Wang, Hujun; Wang, Yingpeng; Qie, Shuyan (Frontiers in Aging Neuroscience, 2024)
Background: Parkinson's Disease (PD) is a prevalent neurodegenerative disorder that significantly benefits from early diagnosis for effective disease management and intervention. Despite advancements in medical technology, there remains a critical gap in the early and non-invasive detection of PD. Current diagnostic methods are often invasive, expensive, or late in identifying the disease, leading to missed opportunities for early intervention. Objective: The goal of this study is to explore the efficiency and accuracy of combining fNIRS technology with machine learning algorithms in diagnosing early-stage PD patients and to evaluate the feasibility of this approach in clinical practice. Method: Using an ETG-4000 type near-infrared brain function imaging instrument, data was collected from 120 PD patients and 60 healthy controls. This cross-sectional study employed a multi-channel mode to monitor cerebral blood oxygen changes.The collected data were processed using a general linear model and β values were extracted. Subsequently, four types of machine learning models were developed for analysis: Support Vector Machine (SVM), K-Nearest Neighbors (K-NN), Random Forest (RF), and Logistic Regression (LR). Additionally, SHAP (SHapley Additive exPlanations) technology was applied to enhance model interpretability. Results: The SVM model demonstrated higher accuracy in differentiating between PD patients and control group (accuracy of 85%, f1 score of 0.85, and an area under the ROC curve of 0.95). SHAP analysis identified the four most contributory channels (CH) as CH01, CH04, CH05, and CH08.The model based on the SVM algorithm exhibited good diagnostic performance in the early detection of PD patients. Future early diagnosis of PD should focus on the Frontopolar Cortex (FPC) region.